Near-Infrared Imaging With Indocyanine Green for the Treatment of Endometriosis: Results From the Gre-Endo Trial - Turco, Luigi Carlo; Vizzielli, Giuseppe; Vargiu, Virginia; Gueli Alletti, Salvatore; De Ninno, Maria; Ferrandina, Gabriella; Pedone Anchora, Luigi; Scambia, Giovanni; Cosentino, Francesco (Frontiers in Oncology, 2021)
Introduction A current challenge for endometriosis surgery is to correctly identify the localizations of disease, especially when small or hidden (occult endometriosis) and to exactly define their real extension. The use of near-infrared radiation imaging (NIR) after injection of indocyanine green (ICG) represents one of the most encouraging method. The aim of this study is to assess the diagnostic value of NIR-ICG imaging in the surgical treatment of endometriosis compared with the standard of treatment. Material and Methods The Gre-Endo trial is a prospective, single arm study (NCT03332004). After exploring the operatory field using the white light (WL) mode, patients were injected with ICG and then observed in NIR mode. All suspected areas were classified and chronicled according to lesions visualized only in WL, NIR-ICG or in the combination of both. Lesion not visualized in WL were considered as suspect occult lesion (s-OcL). In addition, a random control biopsy from an apparent negative peritoneum visualized in WL and NIR-ICG imaging was taken for all patients (control cases). All lesion removed were considered “suspect endometriosis” until pathology. Results Fifty-one patients were enrolled between January-2016 and October-2019. A total of 240 suspected lesions have been identified with both methods (WL+NIR-ICG). Two-hundred and seven (86.2%) lesions out of the overall 240 ones were visualized with WL imaging, and 200 were confirmed to be pathologic (true positive for WL). The remaining 33/240 (13.75%) (false negative for WL) lesions were identified only with NIR-ICG imaging and collected as s-OcL. All 33 s-OcL removed were confirmed to be pathologic (c-OcL=100%). NIR-ICG vision showed PPV of 98.5%, NPV of 87.1%, Se of 87%, and Sp of 98.5%, confirming that this kind of imaging is an excellent diagnostic and screening test (p = 0.001 and p = 0.835, according to the McNemar and Cohen kappa tests, respectively). Conclusions The use of NIR-ICG vision alone and combined with WL showed good results in intraoperative detection-rate and fluorescence guided endometriosis’ surgery. Furthermore, NIR-ICG allowed surgeons to remove occult lesions that otherwise would remain, leading to possible greater postoperative pain and a higher risk of persistence and relapse.